Daucosterol linolenate from Sweet Potato Suppresses MCF7-Xenograft-Tumor Growth through Regulating PI3K/AKT Pathway - Han, Bing; Jiang, Lingmin; Jiang, Pu; Zhou, Deqi; Jia, Xiaoxin; Li, Xuegang; Ye, Xiaoli (Planta Medica, 2020)
Sweet potato is a functional food with potential antitumor properties, but the bioactive constituents and biological mechanisms remain unclear. In this study, we investigated the antitumor effect of daucosterol linolenate extracted from sweet potato and its potential mechanism. An MTT assay indicated that DLA inhibited the proliferation of breast cancer MCF-7 cells but had only weak effects on the proliferation of MDA-MB-231, 4T1, and MCF-10A cells. Flow cytometry analysis revealed that daucosterol linolenate induced apoptosis of MCF-7 cells. Experiments with MCF-7 xenograft in nude mice further confirmed that DLA inhibited tumor growth dose-dependently. After DLA treatment, the expressions of B-cell lymphoma 2 and vascular endothelial growth factor were decreased and that of cleaved caspase 3 was increased as compared to the TC group. DLA also down-regulated the expression of phosphoinositide 3-kinase/protein kinase B and repressed insulin-induced phosphoinositide 3-kinase/protein kinase B activation. Our findings suggest that DLA suppresses breast tumor growth through inactivating the phosphoinositide 3-kinase/protein kinase B pathway.
Keywords: Ipomoea batatas; Convolvulaceae; Daucosterol linolenate; breast cancer; phosphoinositide 3-kinase/protein kinase B